The Effect of Green Credit and Credit Risk on Firm Value with Profitability as Mediating Variable: a Study on Members of the Indonesia Sustainable Finance Initiative (IKBI) during Period of 2019-2024 - Reva Novianti; Ratna Meisa Dai; Zaenal Muttaqin (JURISMA : Jurnal Riset Bisnis & Manajemen, 2026)
This study examines the effect of Green Credit and Credit Risk on Firm Value with Profitability as a mediating variable in 11 IKBI member banks during the 2019–2024 period (66 observations). The research employs panel data regression, path analysis, and the Sobel test to evaluate mediation. The results indicate that green credit has a positive and significant effect on profitability, while credit risk has a negative and significant effect on profitability. However, neither variable has a significant effect on firm value. Profitability is found to have a positive and significant influence on firm value and is able to mediate the effect of credit risk on firm value, but not the effect of green credit. These findings highlight the crucial role of profitability in shaping investor perceptions and enhancing firm value. Keywords: Green Credit; Credit Risk; Profitability; Firm’s Value; IKBI